Sustainable And Ethical Vicegerency In Halal Tourism Practices - Siti Syahirah Saffinee; Mohammad Aizat Jamaludin; Nur LiyanaIzzaty Rosli; Azura Amid; Khairusy Syakirin Has-Yun Hashim (Universiti Utara Malaysia Press, 2024)
Non-Indexed Publication